Taboo Language in “NEIGHBORS 2” Movie - Treanikita, Dewa Ayu Ketut (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p05, 2018)
This his study entitled Taboo Language in “Neighbors 2” Movie are to find out the types of taboo words used in Neighbors 2 movie, to explain the factor influence the used of taboo words in Neighbors 2 movie.The data of this study were analyzed using the theory proposed by Fakuade (2013) as the main theory to identify linguistic taboo and the supporting theory proposed by Jay (1992) to analyze the type of taboo words. Based on Fakuade’s theory there are 5 types of lingistic taboo; they are morality-related linguistic taboo, decorum-related linguistic taboo, veneration-related linguistic taboo. morality-related linguistic taboo, decorum-related linguistic taboo, veneration-related linguistic taboo. However, according to Jay, there are 10 types of taboo words; crusing, profanity, blasphemy, taboo, vulgarity, obscenity, epithet, slang, insult and slurs, and scatology.This study to see the types and factors influence in the movies. In the Neighbors 2 movie has 10 types of taboo words. Therefore, the factorcs influence the used of taboo word found 5 factors. There were 5 factors of taboo words which had been identified, they are: emotion, insulting, crused, dirtyjoke, and shock feeling.